Posttranslational protein modifications in the reproductive system - Sutovsky, Peter (Advances in Experimental Medicine and Biology,, 2014)
This book's aim is to increase the awareness of a great variety of posttranslational modifications in the male and female reproductive system. Some of the most intriguing reproductive strategies, mechanisms, and pathways involving PTM are discussed, with an added angle of evolutionary conservation and diversity. The book also chapters on sperm-egg binding, as well as on histone modification in both the embryo and sperm. Chapters are also devoted to protein ubiquitination, the regulation of sperm function during fertilization in mammals and tubulin modifications in gametes and embryos. There are no other current books on posttranslational protein modifications as they relate to reproduction, making this contribution unique in the field. It is useful for both researchers and graduate students alike.